الرمز الصوفي في شعر البياتي - مستاري, الياس (جامعة الوادي - University of Eloued, 2020)
ملخص: تهدف هذه الدراسة إلى إبراز أهم الشخصيات الصوفية التي وظفها الشاعر عبد الوهاب البياتي في شعره،كالحلاج و ابن عربي،و كيف استطاع أن يجسد رفضهم للواقع الاجتماعي وتمردهم عليه، و معاناتهم من أجل ما يصبون إليه،و كذا التعبير من خلال هذه الرموز الصوفية عن المعاناة الروحية و الجسدية للإنسان المعاصر الذي تتقاطع تجربته مع تجربة هؤلاء المتصوفة. Abstract: This study aims to highlight the most important Sufi personalities that the poet Abd al-Wahhab al-Bayati employed in his poetry, such as al-Hallaj and Ibn Arabi, and how he was able to embody their rejection of social reality and their rebellion against him, their suffering for what they want, and such expression through these Sufi symbols On the spiritual and physical suffering of the modern man whose experience intersects with the experience of these mystics
مقال
Keywords: الرمز الصوفي؛ الشعر البياتي؛ الشعر المعاصر؛ التجربة الشعرية؛ الصوفية